Desperadas ([s.l.] Regal Entertainment, 2008)
A story of four beautiful half-sisters w/ different idiosyncrasies and issues on family and relationship, it portrays the Filipino woman's many trials and how she comes w/ life's unending ups and downs but in the end realizes that all she really needs is love.
VCD
Ruffa Gutierrez, Rufa Mae Quinto, Iza Calzado, Marian Rivera
Keywords: Comedy--Feature.; Feature films